‘Left Adrift and Wondering What the Future Holds’: Learning from Students whose Futures are Drastically Altered by the COVID-19 Pandemic - Wenham, Lucy; Lee, Claire (Critical Education, 2022)
This qualitative study explores the experiences of students whose education was disrupted by school closures during the COVID-19 global pandemic. With a focus on mental health concerns, the article presents the reflections, thoughts and feelings of students whose public examinations were cancelled and who experienced both the abrupt termination of a phase of their formal education and the loss of traditional ways of marking that ending. Findings show that feelings of loss and illegitimacy augment the stress and anxiety surrounding high-stakes tests and their cancellation. There are several implications for policy and practice, if student mental health is to be foregrounded and taken seriously. Communication, dialogue, and possibilities for taking back agency and critical hope may all go some way towards mitigating these mental health concerns. The validity of using re-purposed components to allocate grades is called into question, as are the role and place of high-stakes testing per se.